EFEKTIVITAS PEMBINAAN USAHA INDUSTRI KECIL OLAHAN PANGAN OLEH DINAS KOPERASI UMKM PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN SIGI (STUDI DI KECAMATAN SIGI BIROMARU) - Fausiah, Selfiawaty (Katalogis, 2016)
This study aims at identifying and analyzing The Effectiveness of Small Industrial Business Processed Food Development. This research uses a descriptive qualitative approach, measuring the effectiveness of development based on the opinions of Glen in Adi (2003: 165) which consists of, service development, community involvement and the collaborative creation, concluded that, small industrial business processed food development in Sigi is not effective yet, although there has been an effort from Department of SMEs Cooperatives, Trade and Industry, responding feedbacks and suggestions from businessmen to meet the needs of equipment products, suggesting to join the cooperative, but not fully relieve the burden of the businessmen, especially giving protection (advocacy) on the quality of the product. The development through community engagement to encourage the development of business skills is not effective yet, though there has been given the opportunity of consultation and cooperation among businessmen in increasing independence in business management. There is no seriousness of Local Government to help small processed food industry businesses to provide guidance on an ongoing basis. The guidance through the creation of collaboration is not effective yet, helping the entrepreneurs to establish partnerships with businessmen and finance institutions to obtain additional capital, and especially the ease of solving the problems of licensing Home Industry Food management from Department of Health and product testing in POM regarding to legal products, and the legality of the product right from the Human Rights Ministry, which is verily influencing to the development of the business.